Porch at the Graylyn Estate, 1961. - (:unkn) unknown (Forsyth County Public Library)
WSJ 4-9-61 p.C1.
Porch at the Graylyn Estate, 1961. The photo was used in a feature about Graylyn being the setting for a flower show.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth